An Organismal Model for Gene Regulatory Networks in the Gut-Associated Immune Response - Buckley, Katherine M.; Rast, Jonathan P. (Frontiers in Immunology, 2017)
The gut epithelium is an ancient site of complex communication between the animal immune system and the microbial world. While elements of self-nonself receptors and effector mechanisms differ greatly among animal phyla, some aspects recognition, regulation and response are conserved. A gene regulatory network (GRN) approach provides a means to investigate the nature of this conservation and divergence even when more peripheral functional details remain incompletely understood. To experimentally access this regulatory circuitry, we have developed an organism-wide model of gut-associated bacterial infection in the larval stage of the purple sea urchin. This model provides a morphologically simple system in which to efficiently unravel regulatory connections in an organism that is phylogenetically relevant to immunity in vertebrates. Here, we review the system-wide cellular and transcriptional immune response of the sea urchin larvae. A large set of transcription factors and signal systems, including epithelial expression of IL-17, are important mediators in the activation of the early gut associated response. Many of these have homologs that are active in vertebrate immunity, while others are ancient in animals but absent in vertebrates or specific to echinoderms. This larval model provides a means to experimentally characterize immune function encoded in the sea urchin genome and the regulatory interconnections that control immune response and resolution across the tissues of the organism.